Hope level of primary caregivers of children with epilepsy: current status and influencing factors - Wu, Rui; Zhou, Jinfang (Frontiers in Pediatrics, 2026)
BackgroundPrimary caregivers of children with epilepsy bear long-term care responsibilities and face multiple pressures, which affect their hope level. This survey aimed to evaluate the hope level and associated factors of primary caregivers of children with epilepsy, to provide insights for clinical nursing care.MethodA cross-sectional survey was conducted among primary caregivers of children with epilepsy in a tertiary grade A children's hospital in China. Data were collected using a general information questionnaire and the hope scale, and analyzed via univariate analysis, Pearson correlation analysis, and multiple linear regression analysis.ResultsA total of 248 primary caregivers were included. The overall hope level of caregivers was moderate (total score: 26.25 ± 4.92), with the Intimate Relationship dimension having the lowest score (score rate: 50.44%). Pearson correlation analysis showed that age (r = 0.382), educational level (r = 0.459), and monthly household income (r = 0.417) were positively correlated with hope level (all P < 0.001), while the three scale dimensions (Positive Attitude, Positive Action, Intimate Relationship) all had strong positive correlations with total hope score (all r > 0.85, P < 0.001). Multiple linear regression showed that age (β = 0.193, P < 0.001), marital status (β = −2.876, P < 0.001), residence (β = −3.152, P < 0.001), educational level (β = 1.268, P < 0.001), and monthly household income (β = 1.054, P < 0.001) were independent influencing factors of hope level (model fit: R2 = 0.482, adjusted R2 = 0.467).ConclusionThe hope level of primary caregivers of children with epilepsy was moderate. Younger age, divorced/widowed status, rural residence, lower educational level, and poorer economic conditions were the negative influencing factors. Targeted interventions should be implemented to elevate caregivers’ hope levels.